The social perspective of tattooing and piercing among Tamil speaking communities in Kotahena - Rewathy, K.; Linojah, S. (World Scientific News, 2019)
The study focus on the analysis of the developing deviant culture of Tattooing and Piercing. Most of the people in the modern world involve in tattooing and piercing as considering it as a fashion. But in Asian countries social historical context of being tattooed is different. Especially in Tamil tradition tattooing and piercing has its limitation bound to rituals. Identifying the social perspective of this behavior is essential for the future generation. Qualitative and quantitative methods have been used to analyzed the present situation of the social acceptance and perception of tattoos and piercing. Data collected through primary and secondary data collection methods. Questionnaire survey done among hundred elderly people from the study area. Structured and unstructured interviews done with both tattooed and non-tattooed persons and respondents. According to the social recognition of the phenomenon, the society restrict the tattoo acceptance as fashion. The piercing and tattooing considered to be a undesirable activity of culture. Though earlier the piercing culture was accepted for the Hindu rituals, they were only limited with ears and nose piercing. Tamils consider the fashionable youth behavior of tattooing and piercing as social deviant activity when it has gone beyond the border of rituals and norms. The study provide insight into topic for further research to social perspective affecting tattoo acceptance and the role of fashion. This study limited to a small part of an urban area and a group of Tamil people. Thus, the results cannot be generalized to a vast area. Keywords: Body modification, Deviant Behavior, Piercing, Social perspective, Tattooing